Being human : ethics, environment, and our place in the world - Peterson, Anna Lisa, 1963- (University of California Press, 2001)
This text examines the complex connections among conceptions of human nature, attitudes toward non-human nature, and ethics. Peterson proposes an 'ethical anthropology' that examines how ideas of nature and humanity are bound together in ways that shape the very foundations of cultures.